Work Stress, Organizational Commitment, and Turnover Intention: The Intervening Role of Work Satisfaction - Eri Marlapa; Endri Endri (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: Poor management of human resources can lead to employee discomfort in the workplace, resulting in reduced productivity and diminished benefits for the company. Thus, effective human resource management is crucial to fostering a conducive work environment that enables employees to thrive. Enhanced employee productivity can significantly contribute to the company's advancement. Purpose: This study investigates the impact of work stress and organizational commitment on turnover intention, with job satisfaction as an intervening variable at PT. Jakarta AquariumDesign/methodology/approach: This research method is quantitative causality, using Structural Equation Modeling (SEM) assisted by the Smart PLS statistical method (PLS-SEM) and a Likert measurement scale. Findings/Result: The results in this study show that work stress has a positive and significant effect on turnover intention, while organizational commitment has a positive and significant impact on turnover intention. Another friend revealed that work stress has a positive and significant effect on job satisfaction, and organizational commitment has a positive and significant impact on job satisfaction. Job satisfaction has a negative and significant effect on turnover intention, while organizational commitment has a positive and significant impact on turnover intention through job satisfaction. Organizational commitment influences turnover intention through satisfaction as an intervening variable. Fascinatingly, this study reveals that job-related stress does not diminish employee satisfaction, as stress can serve as a challenge, a stimulus, and a source of fascination for employees. Conclusion: Work stress demonstrates a significant positive impact on turnover intention. Organizational commitment exhibits a positive and statistically significant effect on turnover intention. Additionally, work stress is found to have a positive and important influence on job satisfaction, and organizational commitment similarly has a positive and significant effect on job satisfaction.Originality/value (State of the art): The research uses job satisfaction which acts as a mediating variable that provides new academic insights into human resource strategies related to issues of employee retention and organizational stability. Keywords: work stress, organizational commitment, job satisfaction, turnover intention, PLS-SEM